Former Concert Hall building at the corner of Court Street and Hanover Street, ca. 1875 - Unknown (Tufts Archival Research Center, 2005)
Elevated-view east of the old Concert Hall, located at the northeast corner of Court and Hanover Streets. Signage adorns the facade and the northwest elevation of the building, which faces southwest towards Court Street and northwest towards Hanover Street respectively. Pedestrians are included in the photograph. 2 1/2 x 3 1/4 overall 4 15/16 x 4 3/16 Lantern slides